2011
DOI: 10.1103/physrevb.84.245435
|View full text |Cite
|
Sign up to set email alerts
|

Warping effects in the band and angular-momentum structures of the topological insulator Bi2Te3

Abstract: We performed angle-resolved photoemission (ARPES) experiments on Bi 2 Te 3 with circularly polarized light. ARPES data show very strong circular dichroism, indicating the existence of orbital angular momentum (OAM). Moreover, the alignment of OAM is found to have a strong binding energy dependence. Such energy dependence comes from a relatively strong band warping effect in Bi 2 Te 3 compared to Bi 2 Se 3 . OAM close to the Dirac point has an ideal chiral structure (sin θ ) without an out-of-plane component. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 26 publications
7
30
0
Order By: Relevance
“…3a-c). Such circular dichroism has previously been suggested to probe the spin of the isolated TSS, although the microscopic origin of the dichroism has proved controversial [30][31][32][33][34] . Recently, Park et al 31 proposed the existence of an unquenched local orbital angular momentum (OAM) of the TSS.…”
Section: Resultsmentioning
confidence: 99%
“…3a-c). Such circular dichroism has previously been suggested to probe the spin of the isolated TSS, although the microscopic origin of the dichroism has proved controversial [30][31][32][33][34] . Recently, Park et al 31 proposed the existence of an unquenched local orbital angular momentum (OAM) of the TSS.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that OAM in the initial states should result in CD intensity which is approximately proportional to the inner product of the OAM vector and wave vector of the photon [21,29,30]. This has been shown by numerical simulation of CD-ARPES based on the band calculation [21,22].…”
Section: Complex Orbitals and Cd-arpesmentioning
confidence: 96%
“…Part of these proposals involves the interpretation of the circular dichroism in the angular distribution (CDAD) of ARPES as the spin polarization of TSSs [11][12][13], which, if correct, can significantly improve the efficiency of spin detection. The CDAD effect has also been predicted as an indirect measure of the intrinsic momentum-space orbital-angularmomentum texture of the TSSs [15,16]. These interpretations are, however, unrealistic for several reasons, and one is the dominance of final-state effects in CDAD from TIs that changes sign several times with photon energy [17].…”
Section: Introductionmentioning
confidence: 99%